The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1115/1.4001775
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Dimensional Synthesis and Motion Design of Planar 6R Single-Loop Closed Chains via Constraint Manifold Modification

Abstract: In this paper, we present an interactive, visual design approach for the dimensional synthesis of planar 6R single-loop closed chains for a given rational motion using constraint manifold modification. This approach is implemented in an interactive software tool that provides mechanism designers with an intuitive way to determine the parameters of planar mechanisms, and in the process equips them with an understanding of the design process. The theoretical foundation of this work is based on representing plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…(6). In particular, when a 0 6 ¼ 0, we obtain the constraint manifold of a RR dyad whose projection onto the hyperplane Z 4 ¼ 1 is a hyperboloid of one sheet [7,9,14,21]. Figure 3 shows an example of such a hyperboloid.…”
Section: G-manifolds For Planarmentioning
confidence: 99%
See 2 more Smart Citations
“…(6). In particular, when a 0 6 ¼ 0, we obtain the constraint manifold of a RR dyad whose projection onto the hyperplane Z 4 ¼ 1 is a hyperboloid of one sheet [7,9,14,21]. Figure 3 shows an example of such a hyperboloid.…”
Section: G-manifolds For Planarmentioning
confidence: 99%
“…This includes the definition of the approximation error (called structural error) in the image space, formulation of a least squares problem and application of appropriate numerical methods to find values of the design variables for minimization of the error. Pursuant to Ravani and Roth's kinematic mapping approach for mechanism synthesis, further research has been done by Bodduluri and McCarthy [15], Bodduluri [16], Larochelle [17,18], Ge and Larochelle [19], Husty et al [20], and more recently by Wu et al [21], Purwar and Gupta [22], and Hayes et al [23,24]. Schrcker et al [25] applied the kinematic mapping approach to detect branch defect in the planar four-bar linkage synthesis-a result that can be used in this work as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the definition of the approximation error (called fitting error) in the image space, formulation of a least-squares problem, and application of appropriate numerical methods to find values of the design variables for minimization of the error. Pursuant to Ravani and Roth's kinematic mapping approach for mechanism synthesis, further research has been done by Bodduluri and McCarthy [15], Bodduluri [16], Ge and Larochelle [17], Husty et al [6], Wu et al [18], and Purwar et al [19], both of which have demonstrated a visual, computer graphics approach for multi-degrees-of-freedom mechanism design that exploits the connection between constraint manifold geometry and its apparent effect on the parameters of a mechanism to interactively perform kinematic synthesis. Hayes and Rusu [20] have presented preliminary results for combining type and dimensional synthesis of planar mechanisms for multipose rigid body guidance.…”
Section: Introductionmentioning
confidence: 99%
“…See Ravani and Roth [14] and more recent applications by Hayes [15], Schröcker [16] and Wu and Ge [17]. For spatial motion, Study's kinematic mapping is used to obtain simplified equations for analysis and synthesis, see Husty et al [18] and [19].…”
Section: Introductionmentioning
confidence: 99%